PERKEMBANGAN ARSITEKTUR PADA MASA KOLONIAL DI SURAKARTA TAHUN 1900-1942: TINJAUAN POLITIK, SOSIAL DAN PENDIDIKAN - Dewi, Friska Candra; Saraswati, Ufi; Muntholib, Abdul (Journal of Indonesian History, 2019)
In the colonial period, Surakarta City became one of the centers of government in busy Java. The political influence of the government has an impact on social change and education. The community began to follow an increasingly modern lifestyle, new culture emerged as a form of social and educational change. Meetings of various nationalities and territories divided into two have their own cultural characteristics. It is culture that continues to grow and has an influence on the architectural forms that exist in Surakarta City. The purpose and benefits of this study were to determine the development and influence of colonial culture on architectural art in Surakarta 1900-1942, so that it could become one of the research literature on the history and development of architecture in Surakarta City. The method used in this study is the historical method, namely heuristics, source critical, and interpretation. The development of architecture in Surakarta originated from a traditional city with the influence of the kingdom and thick Javanese culture to become a modern city which began to gain cultural influence in the colonial period. Keywords: Development, Architecture, Surakarta City.